Android-based 4-tier physics test app to identify student misconception profiles - Irnin Agustina Dwi Astuti; Yoga Budi Bhakti; Rendi Prasetya; Zulherman Zulherman (Institute of Advanced Engineering and Science, 2023)
Misconceptions in physics learning are still common at the upper school level. Misconceptions lead to low ability to understand students’ concepts in studying physics. Physics misconceptions experienced by students are difficult to detect. This study aimed to develop an Android-based assessment application with a four-tier diagnostics test instrument that can be used to detect student physics misconceptions early on. Product development is carried out by developing physics instruments for class X, XI, and XII levels and then developing an Android-based assessment application. The results showed that this application received a positive response from teachers and students. In addition, the application is able to detect physics misconceptions experienced by students.